2016
DOI: 10.1099/mgen.0.000045
|View full text |Cite
|
Sign up to set email alerts
|

Towards the complete small RNome of Acinetobacter baumannii

Abstract: In recent years, the Gram-negative bacterium Acinetobacter baumannii has garnered considerable attention for its unprecedented capacity to rapidly develop resistance to antibacterial therapeutics. This is coupled with the seemingly epidemic emergence of new hyper-virulent strains. Although strain-specific differences for A. baumannii isolates have been well described, these studies have primarily focused on proteinaceous factors. At present, only limited publications have investigated the presence and role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…Since we cannot exclude the possibility that the shorter protein is the correct version (meaning the AB5075 annotation is wrong), we analysed AB5075 RNAsequencing data recently generated by our group (Fig. 5d) [32]. In so doing, we demonstrated that, although expressed at a low level, AB5075 mRNA transcripts extended the full length of the ORF, suggesting the upstream start codon is in fact used by the cell.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Since we cannot exclude the possibility that the shorter protein is the correct version (meaning the AB5075 annotation is wrong), we analysed AB5075 RNAsequencing data recently generated by our group (Fig. 5d) [32]. In so doing, we demonstrated that, although expressed at a low level, AB5075 mRNA transcripts extended the full length of the ORF, suggesting the upstream start codon is in fact used by the cell.…”
Section: Resultsmentioning
confidence: 96%
“…Given that our study is largely reliant on accurate genome annotation files, and that we have previously reported inconsistencies in prokaryotic repositories of this type [32, 92], we took an additional approach to our analysis so as to minimize the influence of annotation inaccuracies on our investigations. As such, alongside protein/annotation-based searches, we also performed nucleotide blast analyses (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA sequencing was performed for rpoZ and sigB mutants and their respective parental strains as previously outlined by our group (8,(68)(69)(70). Briefly, RNA was isolated and the quality determined as described for Northern blot experiments.…”
Section: Methodsmentioning
confidence: 99%